Changes over time in serum albumin levels predict outcomes following percutaneous coronary intervention. Issue 4 (April 2020) - Shiyovich, Arthur; Bental, Tamir; Assali, Abid; Vaknin-Assa, Hana; Kornowski, Ran; Perl, Leor
Highlights: Decrease in albumin is associated with worse long-term outcomes following percutaneous coronary intervention. The risk for major adverse cardiac events and all its components increased when albumin decreased. A "dose effect" was observed, with worse outcomes as decrease in albumin was greater. An apparent protective effect with minor changes or increase in albumin was seen. Abstract: Background: Serum albumin (SA) is a powerful prognostic marker in patients with cardiovascular diseases. Objectives: To evaluate the prognostic significance of changes in SA levels among patients that underwent percutaneous coronary intervention (PCI). Methods: Patients who underwent PCI in a tertiary medical center throughout 2004–2017 were considered for the study. Patients with missing SA values within the year before or 5 years after the PCI were excluded from the study as well as those for whom SA values were obtained throughout an acute infection. Changes in albumin were represented by Δalbumin: Albumin before PCI (closest) minus lowest albumin within the 5 years following the PCI. Δalbumin was categorized into 4 categories as follows: ≤0 g/dL, 0-0.5 g/dL, 0.5–1 g/dL, ≥1 g/dL. Primary outcome was major adverse cardiac events (MACE) that included all-cause mortality, non-fatal myocardial infarction, target vessel re-vascularization, and coronary artery bypass surgery. Results: The study included 5449 out of 21, 763 (25%) patients, mean age 66.8 ± 12 years, 26% women. Patients with greater Δalbumin were older with higher prevalence of most cardiovascular risk factors and comorbidity. The follow-up period was 7 years (median), with cumulative MACE rate of 49.5%. MACE rates and the rates of all the MACE components increased gradually with the increase in Δalbumin. Multivariate adjusted analysis showed that Δalbumin is an independent predictor of long-term MACE following PCI [HR = 1.4 (95%CI:1.3-1.6), HR = 2.2 (95%CI:1.9-2.5), HR = 3.8 (95%CI:3.3–4.35) for Δalbumin of 0-0.5 g/dL, 0.5–1 g/dL, ≥1 g/dL, respectively p < 0.001 for all]. Conclusions: A decrease in albumin levels following PCI is an independent prognostic marker of worse long-term outcomes.